The declining mental health of the young and the global disappearance of the unhappiness hump shape in age - David G. Blanchflower; Alex Bryson; Xiaowei Xu (PLoS ONE, 2025)
Across many studies subjective well-being has followed a U-shape in age, declining until people reach middle-age, only to rebound subsequently. Ill-being has followed a mirror-imaged hump-shape. Using graphical and regression analyses of repeat cross-sectional micro-data from the United States and the United Kingdom, we show this empirical regularity has been replaced by a monotonic decrease in ill-being by age. The reason for the change is the deterioration in young people’s mental health both absolutely and relative to older people. Pooling Global Minds data across 44 countries, including the United States and the United Kingdom, over the period 2020–2025 we confirm that ill-being is no longer hump-shaped in age but now decreases in age. JEL Codes: I31; I38